Local Authority of Mining in the Perspective of Regional Autonomy (The Analysis of Conflict Potential Management for Gold Mining Community in Paboya, Palu) - Intam Kurnia (e-2477-1929)
The objective of this research is to answer questions of: 1) What is the division of affairs between government structures in terms of mining affairs in the City of Palu; 2) How mining affairs is being managed in the City of Palu; 3) What are the conflicts between government, business people, and community around the mining area in managing mining in the City of Palu; 4) What are the alternatives to manage effective and efficient mining affairs. This research is suing qualitative approach with the intention to analyze some phenomenon regarding the organization of mining affairs, conflicts of mining, and the alternative solutions. Data collection technique is conducted through interviews, observations, and documentations. The outcome of the research shows that: 1) there is an overlap in the organization of mining affairs between government structures, both in politics and administration. In the organization of mining affairs in Poboya, political aspect is being prioritized than the administrative aspect. It is proofed by the dominance of downstream approach (conflict resolution of Poboya minefield) done by city government, rather than upstream approach (policy making) that ensures the management of public mining in Poboya; 2) the lack of roles and stakeholders in the process of formulating mining policy, institutional issues, and the weakness of community participation in formulating mining programs; 3) Regarding uncertainties within the community and business people in managing minefield, each of them feels that they have the right to manage or exploit the mining areal based on their authority upon the mining area of Poboya. This research recommends the need to organize the mining affairs which refers to the importance of clear management on government structure. The political aspect is highlighting the need to do cooperative formulation, creating mining policy which is based on reality, filtering aspiration and creating rules. While the administrative aspect is highlighting the programs of control coordination, a good and environmental-friendly mining, clear regulation, as well as coordination between actors who are involved in the organization of mining affairs in the City of Palu.Keywords: decentralization, mining affairs and conflict